Legal Protection for Digital Wallet Users Regarding Transactions Without Verification - Alifia Aisya Hikma; Marwah (Hasanuddin Civil and Bussiness Law Review, 2026)
This research aims to analyze the legal protection available to digital wallet users who experience balance reductions due to unverified transactions and to examine Bank Indonesia’s supervision of digital wallet services. This research employs an empirical legal approach using both primary and secondary data. The data collected were then processed and analyzed descriptively and qualitatively to draw conclusions and provide recommendations for addressing the identified issues. The research shows that legal protection for digital wallet users who experience balance reductions due to unverified transactions is regulated under Article 4 letter h of the Consumer Protection Act, Article 48 letters i and j of PBI 3/2023, Article 177 letter c of PBI 23/6/PBI/2021, and Article 32 of PADG 20/2023. Affected users may file complaints with Bank Indonesia under Article 52 of PBI 3/2023, which will be addressed through education, consultation, and facilitation. Bank Indonesia's supervision is carried out through both direct and indirect methods, including the evaluation of reports, self-assessments, documents, and periodic or ad hoc inspections to ensure that service providers implement consumer protection principles in all business activities.